2018
DOI: 10.1371/journal.pone.0203594
|View full text |Cite
|
Sign up to set email alerts
|

Twitter use in scientific communication revealed by visualization of information spreading by influencers within half a year after the Fukushima Daiichi nuclear power plant accident

Abstract: Scientific communication through social media, particularly Twitter has been gaining importance in recent years. As such, it is critical to understand how information is transmitted and dispersed through outlets such as Twitter, particularly in emergency situations where there is an urgent need to relay scientific information. The purpose of this study is to examine how original tweets and retweets on Twitter were used to diffuse radiation related information after the Fukushima Daiichi nuclear power plant acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 24 publications
(15 reference statements)
1
28
0
Order By: Relevance
“…The maximum tweet count per day reached 1,343,045 tweets on the election day: June 5. In terms of the Fukushima Daiichi Nuclear Power Plant accident, which was directly related to life-threatening and energy problems, approximately 25 million tweets were posted within a span of 195 days, and the maximum tweet count per day was more than 640,000 (Tsubokura et al, 2018). Comparing these politically and socially hot topics, the issue on labeling of genome-edited food seemed to draw less attention on Twitter.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum tweet count per day reached 1,343,045 tweets on the election day: June 5. In terms of the Fukushima Daiichi Nuclear Power Plant accident, which was directly related to life-threatening and energy problems, approximately 25 million tweets were posted within a span of 195 days, and the maximum tweet count per day was more than 640,000 (Tsubokura et al, 2018). Comparing these politically and socially hot topics, the issue on labeling of genome-edited food seemed to draw less attention on Twitter.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also reported on misleading health information on social media [23,25]. After the Fukushima nuclear accident, 80% of the total number of tweets on Twitter were created by 2% of influential accounts [26]. However, YouTube users can find varied videos when they conduct searches with keywords.…”
Section: Principal Findingsmentioning
confidence: 99%
“…In Japan, academic research has mostly focused on the role of social media and influencers in the aftermath of natural disasters like the 2011 Tōhoku earthquake and tsunami (Hashimoto and Ohama, 2014; Tsubokura et al, 2018). A study on the diffusion of scientific information on Twitter found that the vast majority of tweets concerning the nuclear disaster had been initially produced by a small group of influencers, who have since been deemed important collaborators for diffusing reliable information to the general public (Tsubokura et al, 2018: 2).…”
Section: Role Of Influencers In the Information Landscapementioning
confidence: 99%
“…In Japan, academic research has mostly focused on the role of social media and influencers in the aftermath of natural disasters like the 2011 Tōhoku earthquake and tsunami (Hashimoto and Ohama, 2014; Tsubokura et al, 2018). A study on the diffusion of scientific information on Twitter found that the vast majority of tweets concerning the nuclear disaster had been initially produced by a small group of influencers, who have since been deemed important collaborators for diffusing reliable information to the general public (Tsubokura et al, 2018: 2). We can observe an alternative approach to Japanese social media research in the work of anthropologist Gabriella Lukács (2020), whose study explored different categories of female influencers – for example, net idols and bloggers – calling attention to the processes of value extraction that have affected women in the Japanese digital economy.…”
Section: Role Of Influencers In the Information Landscapementioning
confidence: 99%